Association Between Coccidia and Intestinal Helminths in Broiler Chickens - Franceschi, Mauricio E. De; Barrios, Hebe A.; Filippini, Olga S. (International Journal of Poultry Science, 2007)
The system of extreme intensivity in which commercial birds are bred favors the simultaneous presentation of many illnesses. Coccidiosis has a big economical importance and it has been studied in combination with a great number of affections like salmonellosis, Marek´s disease clostridiosis, reovirosis, among others. Until now, the relation between the presentation of coccidiosis and other intestinal parasites was not studied. We recollected systematically data on broiler chickens for the period of ten years. The search of coccidios was made by the Serial Scraping Method of the Intestinal Mucosa (SSMIM), while the macroscopical parasites were identified at first. The 80 % of the samples were positive to coccidiosis. From them, the 58.5% were sub-clinical, the 34% clinical degree 1 and the 7.5% clinical degree 2 and 3; these proportions were maintained during the study. In all the analyzed samples the duodenum were affected. The other intestinal sectors were always involved in form combined with this. We found 25 % of farms infected with variable proportions of ascaris, heterakis and tapeworms throughout the 10 years, despite first half of the period showed a greater frequency of findings. The results suggest that throughout the period studied existed a high prevalence of coccidiosis, being the subclinic and clinic presentations slight (degree 1) those of greater frequency. Duodenum was affected in the 100% of the chickens in where we found coccidian indicating the very probable preeminence of Eimeria acervulina. It was not detected the relation between the macroscopical presentation of coccidiosis and intestinal parasites.